Professional engagement of a music art teacher as a resource of their creative productivity - Bolshakova, Tetiana (Professional Art Education, 2026)
The purpose of the study is to theoretically substantiate the essence, structure, and functional significance of professional engagement of a music art teacher as a resource of their creative productivity in the context of contemporary art education. The research methods include theoretical analysis, generalization and systematization of scientific approaches to the study of professional engagement, comparative analysis of theoretical concepts, and the method of theoretical modeling for constructing the author’s structure of the studied phenomenon. The scientific significance of the study lies in expanding the understanding of professional engagement as an integrative psychological and pedagogical phenomenon in the context of art education, as well as in developing an authorial model of professional engagement of a music art teacher that takes into account the specifics of combining pedagogical and creative-performing activities. The results of the study indicate that the professional engagement of a music art teacher has a complex multicomponent structure, which includes emotional-energetic, motivational-value, cognitive-interpretative, and behavioral-activity components. A system of mechanisms for its formation has been identified, including motivational-meaningful, emotional-aesthetic, cognitive-reflective, behavioral-activity, and socio-communicative mechanisms that ensure the integration of personal internal resources in the process of artistic and pedagogical activity. It has been substantiated that professional engagement acts as a system-forming resource of creative productivity, contributing to the activation of cognitive processes, enhancement of emotional expressiveness, formation of an individual style of activity, and development of innovativeness. Conclusions. The professional engagement of a music art teacher is a key resource of their creative productivity, ensuring the integration of emotional, motivational, and cognitive-activity processes and contributing to the effectiveness of artistic and pedagogical activity. The obtained results can be used in the system of professional training and advanced training of teachers of artistic disciplines.